The national and cultural character of the concept «Woman» - Sagidolda Г.С.; Abdimaulen Г.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
One of the topics that will forever be studied in science and society is the issue of women. Names related to the concept of «woman» in the knowledge of the Kazakh people, language units, lexico-phraseological, paremiological units, concepts formed in the concept of the people, data confirming the concept of «woman» in modern artistic texts, which allow us to recognize the taste, attitude, feelings, psychology, diverse features of Kazakh women, determine their place in Kazakh culture. The most important issue is the definition of the role and place of woman in the life of society, in national culture, in the linguistic and cultural direction of the language data that characterize her, and the interpretation of the lexical-semantic, conceptual content of the concept of woman in the context of the level of background knowledge. The article considers the contribution of the phraseological system of the language to the modernization of the mentality inherent in a particular linguistic and cultural community. The concept of «woman» is based on the national character of the concept of woman as a whole, the linguistic and cultural features of the social consciousness and mentality of the two peoples, national values and views on the world, which are embodied in the phraseological fragment of the Kazakh world image. The research is aimed at a deeper understanding of the meaning of phraseological phrases used in the Kazakh language. Phraseological phrases indicate the place occupied by the female subject in modern society